Analytic Performance of Monopulse Spread Spectrum Tracking System in Multiple-target Scenario. (January 2016) - Cong, Bo; Qu, Yuanxin; Zhang, Yongliang
Abstract: With the application of spread spectrum technique in satellite tracking, the accuracy of CDMA-based multiple-target tracking needs to be analyzed. In this paper, we present the analytic form of the multiple-target tracking performance through mathematical deduction, together with simulation results.